PERANCANGAN SISTEM INFORMASI SASARAN KINERJA PEGAWAI DI UNIVERSITAS NEGERI PADANG - Fauzi Rahman; Efrizon Efrizon (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
To produce employees who have the ASN profession, there is a need for ASN guidance. As a first step in conducting coaching, an assessment of the performance of the ASN is needed. This assessment will later be used as material for consideration for promotion, placement in position, transfer, education and training, and consideration in remuneration payments. The work performance assessment of Civil Servants is carried out systematically, with emphasis on the level of achievement of employee work targets or the level of achievement of work outcomes that have been prepared and agreed upon between Civil Servants and Appraisal Officials. The performance appraisal of civil servants themselves has two elements of assessment, namely the first from the Employee Work Target (SKP) and the second from Work Behavior. The problem that occurs is that the assessment of work performance is difficult because not all ASNs in the Universitas Negeri Padang environment keep a diary properly. In addition, the problems that often occur are diaries that are manually created require a lot of paper and ink, this is considered not economical and efficient and when archived there is a possibility of being scattered or lost. From the problems mentioned above, an employee performance target information system was developed at Universitas Negeri Padang. With this application, it can facilitate ASN in preparing and filing SKP, making daily notes, and simplifying employee performance appraisals.Keywords: Development, Information Systems, SKP, Universitas Negeri Padang.